Emergency Medical Care in Case of Drowning and Measures to Restore the Patient's Health: Perawatan Medis Darurat Jika Tenggelam dan Tindakan untuk Memulihkan Kesehatan Pasien - Salomov Shoxabbos Nozimjon o’g’li (Academia Open, 2022)
This study presents an in-depth evaluation of first aid measures employed by teachers in educational settings, with a focus on optimizing response strategies. The goals of this research were to assess the efficacy of teacher-led first aid interventions, investigate the methods employed, analyze the outcomes achieved, and derive practical implications for enhancing emergency preparedness. A comprehensive analysis of various first aid techniques implemented by teachers yielded insightful results, highlighting the importance of prompt action, accurate assessment, and appropriate treatment in ensuring positive outcomes. The implications of these findings underscore the need for targeted training programs and improved access to up-to-date medical resources, equipping educators with the necessary skills and knowledge to effectively manage medical emergencies in the classroom, ultimately safeguarding student well-being. Highlights: Comprehensive assessment: This study offers a thorough evaluation of first aid measures implemented by teachers, providing a comprehensive analysis of the strategies employed in educational settings. Efficacy and outcomes: The research investigates the effectiveness of teacher-led first aid interventions and analyzes the achieved outcomes, emphasizing the significance of prompt action, accurate assessment, and appropriate treatment. Implications for enhanced preparedness: The findings underscore the need for targeted training programs and improved access to medical resources, highlighting the importance of equipping educators with the necessary skills and knowledge to effectively manage medical emergencies, thereby enhancing emergency preparedness in educational environments Keywords: First aid measures, teacher-implemented strategies, educational settings, optimization, emergency preparedness.